MODEL POPULASI PENDEKATAN PERTUMBUHAN DAN INDEKS KONDISI Harpiosquilla raphidea WAKTU TANGKAPAN PADA PAGI HARI DI PERAIRAN UTARA PULAU TARAKAN - Tomy Chandra; Gazali Salim; Dhimas wiharyanto (Jurnal Harpodon Borneo, 2015)
The research method uses descriptive method. The main variables to be measured in this study are variable length relationship in total and the total weight, variable carapace length and weight of the meat, the correlation length variable weight, condition index variable. Secondary variables of physical and chemical parameters will be measured in this study were pH, DO, temperature, salinity and brightness. Data collection techniques using survey research design. The sampling technique shrimp H.raphidea use way of "sampling". Raphidea Harpiosquilla shrimp sampling using purposive sampling method. Sampling was performed 12 times in three months as many as 343 samples (213 males and 130 females) are expected to represent the population of shrimp in the waters Juata Harpiosquilla raphidea Tarakan City. Environmental aspects Harpiosquilla raphidea for shrimp in the waters of the Tarakan city juata analysis such as pH, DO, salinity, temperature, and brightness. Results of research on the growth model allometri based (relations total length and total weight) and (relationship carapace length and weight of meat) of shrimp H.raphidea gender Male and Female allometri found to have growth is negative with the value of b 3. Results The percentage of the value of research data processing conditions index, By (Relationship Length and Weight Total Total) of H.raphidea Male and Female-dominated form of body fat. Based (carapace length and weight relationship Meat) H.raphidea maledominated form of body fat and lean body shape female dominated. Results of research on the sex ratio of shrimp H.raphidea sex Males and Females were 62% and 38% which is 1.6: 1.  Keywords : population, growth, conditions index, morning, Tarakan